2022
DOI: 10.1155/2022/7149686
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Biology, Detection Techniques, and Clinical Applications of Circulating Tumor Cells

Abstract: Circulating tumor cells (CTCs) play a crucial role in tumor recurrence and metastasis, and their early detection has shown remarkable benefits in clinical theranostics. However, CTCs are extremely rare, thus detecting them in the blood is very challenging. New CTC detection techniques are continuously being developed, enabling deeper analysis of CTC biology and potential clinical application. This article reviews current CTC detection techniques and their clinical application. CTCs have provided, and will cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 138 publications
0
1
0
Order By: Relevance
“…CTCs attracted widespread interest as a minimally invasive tumor marker used for cancer diagnosis, prognosis, and prediction of therapeutic response in breast cancer and other tumors. Moreover, it can provide novel insights into metastasis and potential therapeutic targets [3,[45][46][47]. Recent studies have shown that CTCs present a clonal heterogeneity with only a subset of the cells having the ability to initiate metastasis [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…CTCs attracted widespread interest as a minimally invasive tumor marker used for cancer diagnosis, prognosis, and prediction of therapeutic response in breast cancer and other tumors. Moreover, it can provide novel insights into metastasis and potential therapeutic targets [3,[45][46][47]. Recent studies have shown that CTCs present a clonal heterogeneity with only a subset of the cells having the ability to initiate metastasis [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, investigations have been carried out to ascertain whether the biological insights derived from CTCs hold the potential to advance patient care. Indeed, it is crucial to give significant attention to circulating tumor cells (CTCs), viewing them not merely as progression disease (PD) endpoints, but also recognizing their role as prognostic indicators and as biomarkers for predicting and assessing responses at intermediate endpoints [53]. Various investigations have substantiated the prognostic relevance of CTC counts across diverse tumor types.…”
Section: Clinical Utility Of Ctcs: Emergence As Multifunctional Bioma...mentioning
confidence: 99%